2015
DOI: 10.1007/s11695-015-1613-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reshaping Following Bariatric Surgery

Abstract: Breast reshaping in post-bariatric patients is a big challenge and only a careful analysis of the degree of ptosis of the breast, its volume and shape, and a clear communication with the patients about the real outcomes and complications can make the winning surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similar to our findings, Gurunluoglu et al revealed an improvement of satisfaction with breast (75.2±11.0), psycho-social (66.3±10.2), and sexual well-being (65.7±16.3) after breast implant removal and "autoaugmentation" using an inferior pedicle dermoglandular flap including 20 patients (25). A further study observed statistically significant improvements in satisfaction with breast (89.2±20.7), psychosocial (86.1±22.7), sexual (73.3±16.6) and physical well-being (86.3±14.6) after any breast reshaping procedures including "autoaugmentation", breast reduction, mastopexy and silicone implants, however satisfaction scores were not distinguished between the different reshaping techniques (26).…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our findings, Gurunluoglu et al revealed an improvement of satisfaction with breast (75.2±11.0), psycho-social (66.3±10.2), and sexual well-being (65.7±16.3) after breast implant removal and "autoaugmentation" using an inferior pedicle dermoglandular flap including 20 patients (25). A further study observed statistically significant improvements in satisfaction with breast (89.2±20.7), psychosocial (86.1±22.7), sexual (73.3±16.6) and physical well-being (86.3±14.6) after any breast reshaping procedures including "autoaugmentation", breast reduction, mastopexy and silicone implants, however satisfaction scores were not distinguished between the different reshaping techniques (26).…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge, the existing literature concerning patient satisfaction after mastopexy autoaugmentation is limited. Vindigni et al reported an improvement in patient satisfaction after breast reshaping in patients with massive weight loss using different procedures including implant augmentation, traditional mastopexy, breast reduction, and autoaugmentation [24].…”
Section: Discussionmentioning
confidence: 99%
“…(10) Treatment of the post-bariatric breast is fundamentally a breast reshaping, and the favorite technique is mastopexy with parenchymal remodeling and augmentation with autologous tissue. (35) Breast reshaping in post-bariatric patients is particularly challenging because of severe tissue atrophy and skin excess. The histological alterations confer the highest clinical consequences to this area: highest degrees of true ptosis, deflated and flattened glands, and totally inelastic covering tissues.…”
Section: Discussionmentioning
confidence: 99%